Exposure to the US news media, religion and the Malaysians' students attitudes towards the United States - Tamam, Ezhar; Wan Abas, Wan Anita (Universiti Putra Malaysia Press, 2006)
This study primarily seeks to determine the influence of exposure to US media and religion on Malaysian students' attitudes toward the United States of America. A total of 133 male and 158 female students (181 were Muslims and 105 non-Muslims) participated in a self-administered survey assessing their attitudes toward the US. The findings showed that ambivalent tendencies reflected in the majority of students' seeming dislike towards American idea and values, and 'concept of democracy' that are slowly seeping into the Malaysian way of life. On the other hand, the same respondents also welcomed American music and movies, its technological and scientific advancement, and the 'work ethics' that American capitalism claims to adhere. No significant difference was found on all four items on attitudes toward US between respondents who were exposed to CNN and US newsmagazine from those who were not exposed to these US media, except on attitudes towards US technological and scientific advancement. The influence of religion seems more prominent. Muslim and non-Muslim respondents significantly differed in their preference for American ideas and customs, music and movies, and technological as well as scientific progress. However, attitude towards the American way of doing business was well appreciated. The pattern of findings suggests that foreign media exposure is not necessarily a good measure of foreign cultural orientation, but religion seem to be a powerful factor of audience attitudinal reaction to international cultural exchange.